2010
DOI: 10.1136/emj.2009.089508
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Canadian c-spine rule in the UK emergency department setting

Abstract: The CCR can be applied successfully in the UK. Had the CCR been in use during the study period, a 17.4% reduction in radiography could have been achieved without compromising patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
0
16
0
4
Order By: Relevance
“…In the 8 studies that used different reference tests, patients who did not undergo imaging were followed up with either the 14-day proxy 2,13,19,22,23,26 or the 21-day surveillance strategy. 19,21,24 With the 14-day proxy method, patients are contacted by a registered nurse 14 days after discharge and asked 8 questions about pain and return to function.…”
Section: E868mentioning
confidence: 99%
See 2 more Smart Citations
“…In the 8 studies that used different reference tests, patients who did not undergo imaging were followed up with either the 14-day proxy 2,13,19,22,23,26 or the 21-day surveillance strategy. 19,21,24 With the 14-day proxy method, patients are contacted by a registered nurse 14 days after discharge and asked 8 questions about pain and return to function.…”
Section: E868mentioning
confidence: 99%
“…Of the 9 studies that assessed the Canadian Cspine rule, 4 were prospective studies 2,13,21,23 that aimed to assess the rule in its entirety; 4 prospectively applied a modified version of the rule; 19,22,24,25 and 1 was a retrospective study. 20 The sensitivity of the Canadian C-spine rule ranged from 0.90 to 1.0, while the specificity ranged from 0.01 to 0.77 ( Figure 2).…”
Section: Canadian C-spine Rulementioning
confidence: 99%
See 1 more Smart Citation
“…197 High-quality studies have shown that physicians in the ED can safely use the CCR as well as the NEXUS (National Emergency X-Radiography Utilization Study) criteria to rule out CSI. 23,26,198 Studies have also shown that the CCR is more sensitive and specific than the NEXUS criteria, and that using the CCR results in lower rates of radiological examinations. [199][200][201] Further, the CCR can be used with similar accuracy and reliability by triage nurses in the ED and paramedics in the prehospital setting.…”
mentioning
confidence: 99%
“…The investigations giving rise to these criteria were undertaken because of acknowledgment of negative findings in an overwhelming majority of imaging studies in acute cervical trauma and of the accompanying unwarranted expenses and use of emergency department time and resources. 8,44,45,99,104 In the presence of positive clinical assessment findings derived from the CCSR 18,117,118 or the NEXUS-LRR, 55,91 computed tomography (CT) is the initial imaging modality determined to be "usually appropriate" because of the primary concern for fracture or other destabilizing injury (eg, zygapophyseal joint dislocation) in adults. 11,24,25 In cases of suspected cervical vascular injury, either CT or magnetic resonance angiography may be used to evaluate the extent of vessel injury and perfusion by contrast distribution.…”
Section: Imaging Clinical Decision Rules Cmentioning
confidence: 99%